2018
DOI: 10.3389/fnagi.2018.00160
|View full text |Cite
|
Sign up to set email alerts
|

Partial Depletion of Peripheral M1 Macrophages Reverses Motor Deficits in MPTP-Treated Mouse by Suppressing Neuroinflammation and Dopaminergic Neurodegeneration

Abstract: Background: Neuroinflammation plays an important role in the pathogenesis of Parkinson's disease (PD). Inflammatory cytokines in the peripheral immune system can induce neuroinflammation in central nervous system (CNS). Whether the peripheral immune system is involved in PD is unclear. The present study investigated the contribution of the peripheral immune system to the neuronal loss in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine(MPTP) model of PD.Methods: MPTP was intraperitoneally injected into mice to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…to deplete peripheral macrophages. This macrophage depletion method had been proven to be reliable and widely used in many models [41,46]. We also proved that the macrophage depletion e ciency of the liposome (Supplemental Figure 3).…”
Section: Macrophages Depletion Alleviatedcolonic Myenteric Neurons Insupporting
confidence: 62%
See 2 more Smart Citations
“…to deplete peripheral macrophages. This macrophage depletion method had been proven to be reliable and widely used in many models [41,46]. We also proved that the macrophage depletion e ciency of the liposome (Supplemental Figure 3).…”
Section: Macrophages Depletion Alleviatedcolonic Myenteric Neurons Insupporting
confidence: 62%
“…To further determine the role of macrophages in neurons injury following system treatment of vincristine, we conducted a direct veri cation through in vivo macrophage depletion. We speci cally depleted macrophages of mice by the clodronate liposomes, this method had been proven to be reliable and widely used in stroke models [46] and Parkinson's disease [41]. Our results showed that continuous macrophage depletion signi cantly reduced colonic proin ammatory factors and mitigated colonic myenteric neurons injury.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, it has previously been revealed that TNF -α mRNA expression is significantly mitigated by melatonin treatment [ 27 ]. Yan et al [ 28 ] found that clodronate liposome treatment reduced the mRNA expression of inflammatory cytokines, such as TNF -α, IL -1β, and IL -6, in the striatum and SNpc. Research has also shown that treatment with pioglitazone attenuates the activation of microglia and astrocytes in the striatum and SNpc in MPTP-intoxicated mice [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is modulated by a number of mediators including cytokines, chemokines, prostaglandins and substance P (1). The central nervous system (CNS) was reported to respond to peripheral inflammatory stimuli by initiating a local inflammatory response, also known as neuroinflammation (2). There are numerous critical features in the development of neuroinflammation, including glial activation, the accumulation of pro-inflammatory cytokines and the expression of adhesion molecules (1,3,4).…”
Section: Introductionmentioning
confidence: 99%